2008
DOI: 10.1136/aim.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electrostimulation of Acupuncture Points for Sedation of Critically Ill Patients in the Intensive Care Unit – a Pilot Study

Abstract: Background This is a pilot study to investigate the effects of electrostimulation of acupuncture points on sedation and the dose of sedatives in the Intensive Care Unit. Methods Electrostimulation of acupuncture points was performed on 12 critically ill patients requiring sedation for mechanical ventilation. Electrostimulation was applied by point surface electrodes at LI4, ST36, HT7 and LR3 points for 20 minutes every hour for 12 hours using dense dispersed mode with a current frequency of 10-100Hz and maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…Não temos evidências de que a TENS tenha atuado exclusivamente nos pontos acupunturais, pois os eletrodos possuem área que abrange o nervo mediano, ulnar e radial, mas, pelo posicionamento dos eletrodos em cima dos acupontos, sabemos que a corrente elétrica passou por eles. Isto corrobora um estudo de Nayak et al (27), que conseguiram um aumento no estado de sedação de pacientes de UTI, sem qualquer efeito colateral, com eletroestimulação superficial de acupontos.…”
Section: Discussionunclassified
“…Não temos evidências de que a TENS tenha atuado exclusivamente nos pontos acupunturais, pois os eletrodos possuem área que abrange o nervo mediano, ulnar e radial, mas, pelo posicionamento dos eletrodos em cima dos acupontos, sabemos que a corrente elétrica passou por eles. Isto corrobora um estudo de Nayak et al (27), que conseguiram um aumento no estado de sedação de pacientes de UTI, sem qualquer efeito colateral, com eletroestimulação superficial de acupontos.…”
Section: Discussionunclassified
“…Sedative drugs can even induce true physical dependence and psychological dependence, with or without addiction, leading to drug withdrawal diffi culties, increasing the economic burden of long-term ICU patients. This could enhance the role of acupuncture in treatment for sedation 35 and for analgesia. 36 Numerous studies have demonstrated that the nervous system, neurotransmitters and endogenous substances may respond to needling stimulation and electrical acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…1 A pilot study has previously implied a role for acupuncture in sedation of critically ill patients. 2 Surface electrostimulation (at LI4, ST36, HT7 and LR3) signifi cantly reduced the amount of propofol used to sedate 12 patients. 2 In that study, sedation was assessed using a subjective scoring system (Sheffi eld Sedation Scale).…”
mentioning
confidence: 99%
“…2 Surface electrostimulation (at LI4, ST36, HT7 and LR3) signifi cantly reduced the amount of propofol used to sedate 12 patients. 2 In that study, sedation was assessed using a subjective scoring system (Sheffi eld Sedation Scale). 2 Zheng et al used BIS and the Ramsay scoring system to guide sedation in 45 patients in intensive care.…”
mentioning
confidence: 99%
See 1 more Smart Citation